Basic researchMaternal palmvitee administration reduced plasma total bilirubin and uridine diphosphate glucuronyltransferase activity in hyperbilirubinaemic rat neonates - Kamisah, Yusof; Norhayati, Mohd Y.; Mazliadiyana, Mazlan; Zakri, Bustaman; Zalizawati, Din S.; Asmadi, Ahmad Y. (Archives of Medical Science, 2008)
Introduction: Hyperbilirubinaemia (jaundice) is common during the first days of postnatal life. a-Tocopherol was reported to decrease serum total bilirubin in jaundiced human newborns. This study was conducted to investigate the effect of maternal palmvitee administration on hyperbilirubinaemia induced by d-aminolevulinic acid (ALA) in rat neonates. Material and methods: Twenty-four successfully mated female Wistar rats were divided into three groups. They were given 50 or 200 mg palmvitee/kg body weight orally once daily from day 1 of pregnancy to delivery, while the other group was given olive oil (control). At postnatal day 14 (the optimal age to induce hyperbilirubinaemia as obtained earlier), the pups born to four dams of each group were induced with hyperbilirubinaemia, while the rest were given vehicle. Twenty-four hours after the induction, the neonates were sacrificed. Plasma total bilirubin, hepatic thiobarbituric acid reactive substance (TBARS), uridine diphosphate glucuronyltransferase (UGT) activity and vitamin E content were determined in the neonates. Results: ALA administration increased plasma total bilirubin. In the palmvitee-treated groups, plasma total bilirubin was lower than in the controls (0.19±0.01 and 0.10±0.01 vs. 0.35±0.18, p<0.05). ALA did not affect the hepatic UGT, but it was reduced in the palmvitee-treated groups (0.71±0.10 and 0.55±0.02 vs. 0.92±0.07, p<0.05). Neither ALA nor palmvitee influenced hepatic TBARS level. Maternal pretreatment with 200 mg/kg palmvitee increased the neonatal hepatic vitamin E content. Conclusions: The maternal administration of palmvitee showed a protective effect on hyperbilirubinaemia. However, this administration could lead to decreased hepatic glucuronidation activity in rat neonates.